Analisis Formalistik pada Poster Film Cut Nyak Dhien1988 Edisi Restorasi 2021 - Asrinaldi Ray; Fentisari Destri Sucipto (Universitas Bumigora, 2023)
The Cut Nyak Dhien Movie in 1988 has been restored and released a movie poster using a new design as a one of its promotion media. Poster on movie serve to conver relevant information related to its movie. The research problem in this study is how formalistic analysis uses design elements. The purpose of this research is to describe the Cut Nyak Dhien movie poster using formalistic analysis. The research method used is descriptive qualitative. The results of this studi indicate that the poster does not represent the scenes in the Cut Nyak Dhien movie. This poster uses a sepia color which informs the audience that the film has been in production for a long time as well as indicating that the film is a historical themed film. The poster layout shows dynamic elements, balance and emphasis.